Materi Hukum Konvensi Hak Anak dalam Perspektif Islam - Siti Dalilah Candrawati (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2007)
Children is important in regeneration of a nation, a mandate from as well as gift from God Almighty. Children are equipped with basic human rights as those owned by grown ups. In reality and in certain circumstances, childern are objects of violence and unjust attitude. This situation is caused and worsened by discrimation and violence. Many children suffer those unjust treatments because they are poor, deserted, and homeless. A legal system which is not aware of their rights and needs also contributes to this ill treatment. All aforementioned accumulation of bad sitiations has awakened nations to protect children, which is legally-based or otherwise. The Convention on the Right of the Child is an internationally-signed document for children protection which is endorsed by General Assembly of the UN on November the 20th 1989. in that document, there are four legal norms for children rights; survival rights, development rights, protection rights, and participation rights. On this children issue, islam as a religion which upholds human rights has shown concepts of comprehensive children rights even before children were born. Such rights have to be uheld by averyone who are bestowed with His gift, be they paretnts, community, and nation.